2021
DOI: 10.31265/jcsw.v16i1.366
|View full text |Cite
|
Sign up to set email alerts
|

The significance of interprofessional and interagency collaboration in reintegration after prison

Abstract: The Norwegian Correctional Service is well known for its focus on rehabilitation and the humane treatment of offenders. However, welfare issues and comorbidity are overrepresented among offenders, and recidivism rates remain unacceptably high. Mental health problems, substance abuse and a lack of housing suggest that offenders need support from a range of services in their reintegration processes. This calls for collaboration between frontline workers, welfare agencies and non-governmental organizations, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…At a high level, experts implicitly agreed, via their consensus view of the importance of 73 indicators as important for students to demonstrate in interprofessional practice, that competency in this area for New Zealand students cannot be distilled easily into one skillset, statement, or competency. This finding aligns with a consensus view in the literature that interprofessional practice is both complex and multifaceted (49)(50)(51). Expert opinion was generally supportive of the indicators obtained from the literature, which may not be surprising given that the experts were highly experienced teaching staff with an interest in the field.…”
Section: Discussionsupporting
confidence: 85%
“…At a high level, experts implicitly agreed, via their consensus view of the importance of 73 indicators as important for students to demonstrate in interprofessional practice, that competency in this area for New Zealand students cannot be distilled easily into one skillset, statement, or competency. This finding aligns with a consensus view in the literature that interprofessional practice is both complex and multifaceted (49)(50)(51). Expert opinion was generally supportive of the indicators obtained from the literature, which may not be surprising given that the experts were highly experienced teaching staff with an interest in the field.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of opportunities for improving program implementation, participants noted that better coordination and communication between the Reintegration Centre and the detention centre might have smoothed the transition from prison to release, a consideration for future iterations of the Reintegration Centre. This siloed approach where the criminal justice system and community services working independently of each other has been documented [108] with the importance of this specific interagency collaboration and coordination also reported in the literature [62, [109][110][111][112]. Other research has demonstrated the value of pre-release peer support in the reentry process.…”
Section: Plos Onementioning
confidence: 94%
“…Finding solutions calls for extensive collaboration between welfare services during the process of reintegrating offenders after prison. Therefore, interprofessional collaboration is a necessity to provide sufficient quality in welfare services to prisoners (Denton, 2014; Friestad and Kjelsberg, 2009; Gisler et al , 2018; Helgesen, 2019; Larsen et al , 2019; Larsen et al , 2021; Larsen and Hean, 2021).…”
Section: Introductionmentioning
confidence: 99%